Islamic law in Malaysia: the challenges of implementation - Trakic, Adnan; Hanifah Haydar Ali Tajuddin (Springer eBook Collection, 2021)
Notes on Contributors -- Foreword -- Preface -- Chapter 1 Challenges in the Implementation of Islamic Law in Malaysia -- Chapter 2 British Administration of Malay Peninsula and Its Impact on the Status of Islamic Law -- Chapter 3 The Status of Islam and Islamic Law in the Malaysian Federal Constitution -- Chapter 4 Islamic Criminal Law -- Chapter 5 Islamic Family Law -- Chapter 6 Islamic Inheritance Law -- Chapter 7 Islamic Commercial Law -- Chapter 8 Islamic Evidence Law -- Chapter 9 Transforming and Globalising the Syariah Judiciary System of Malaysia -- Chapter 10 Implementation of Islamic Law in Malaysia: The Way Forward -- List of Statutes and Regulations -- List of Cases -- Bibliography.